(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduce: Renal transplantation is generally the preferred treatment of patients with end-stage renal. Kidney transplantation is currently the most promising form of renal replacement therapy. Kidney transplantation improves patient survival, quality of life, and cost-effectiveness when compared to dialysis. Hyperglycemia after kidney transplantation is common in both diabetic and non-diabetic patients. Both pretransplant and post-transplant diabetes mellitus are associated with increased kidney allograft failure and mortality. Glucose management may be challenging for kidney transplant recipients. Though post-transplant diabetes mellitus (occurring more than 45 days after transplantation) and its complications are well described, early post-renal transplant hyperglycemia (less than 45 days) similarly puts kidney transplant recipients at risk of infections, rehospitalizations, and graft failure and is not emphasized much in the literature. Objective: The objective of the article is to address a common condition after kidney transplantation, which is early post-transplant hyperglycemia. It also analyzes the pathophysiology, related factors, complications, and the goals of glycemic management in this population. Method: The meta-analysis research method includes articles searched on electronic databases such as PubMed, Journals, and ScienceDirect, covering diabetes, post-transplant hyperglycemia, kidney transplantation, the relationship between pancreatic beta cells and fasting blood glucose, the pathophysiology of hyperglycemia, and some articles related to anti-rejection drug treatments. Early postoperative hyperglycemia after kidney transplantation is associated with complications such as acute rejection, rehospitalization, cardiovascular diseases, infections, and post-transplant diabetes Conclusion: Early postoperative hyperglycemia occurring within 45 days after kidney transplantation increases the risk of rehospitalization for recipients due to infections such as CMV, acute rejection within 20 days post-transplant, cardiovascular events, and post-transplant diabetes. Both patients with and without a history of pre-transplant diabetes can experience early postoperative hyperglycemia. Identifying risk factors such as high pre-transplant blood glucose levels, pre-transplant diabetes, glucocorticoid use, stress, postoperative pain, pre-existing chronic infections like chronic hepatitis C or CMV, and post-transplant infections is crucial for early postoperative hyperglycemia after kidney transplantation. Insulin is currently the standard treatment; however, other new drugs such as GLP-1 RA and SGLT-2 may also be effective, but further research is needed.